Global Distortions to Key Agricultural Commodity Markets - Anderson, Kym (World Bank, Washington, DC, 2017)
The regional books that provided detailed estimates of distortion in developing economies are all country focused. While they include commodity details for their particular country, they are not able to provide an overview for developing countries or high-income countries as a group, or for the world as a whole. This paper seeks to fill this gap. The paper begins by describing the overall project's coverage of 30 major commodities and their importance in regional and global agricultural production and trade. It then summarizes the nominal rates of assistance and consumer tax equivalents for twelve key covered products, together with their gross subsidy/tax equivalents in constant dollars. The paper then examines seven largely non-traded food staples that are nonetheless important food items for poor people in low-income countries. Even though those commodities are only a small share of global production and exports of farm products, they can be crucial to the food security of large segments of developing country societies. The agricultural distortions database lends itself to placing the policies affecting (or ignoring) those products in a broader perspective. The final part of the paper provides another new perspective on the project's database. It seeks to shed light on how relatively distorted are the various commodity markets from the viewpoint of global trade or welfare restrictiveness. This analysis draws on the theory outlined in the previous chapter, but switches the focus from countries to products.